Determinasi Kepemimpinan, Reward dan Punishment Terhadap Kinerja Karyawan di PT. Telkom Indonesia Witel Bandung - Melinda Handayani; Zainur Hidayah; Etty Puji Lestari (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
Giving rewards and punishments is an instrument used to increase employee motivation. However, in its implementation, reward and punishment also have an impact on demotivation. This study aims to determine the effect of leadership, reward, and punishment on employee performance at PT. Telkom Indonesia Witel Bandung. This study uses a quantitative approach, namely through multiple regression analysis. This study used 40 research data obtained from the sampling with the purposive random sampling method. This study also shows that leadership, reward, and punishment significantly affect the performance of the employees of PT. Telkom Indonesia Witel Bandung. Increased leadership, reward, punishment, and leadership, reward, and punishment can be promoted to improve goals.